Area-wide appraisal of drug resistance in trypanosomes infecting cattle in East and Southern Africa - Eisler, M.C.; Ndung'u, J.M.; Murilla, G.; Mdachi, R.M.; Mbwambo, H.; Sinyangwe, L.; Machila, N.; Delespaux, V.; Geerts, S.; Brandt, J.; Peregrine, A.S.; McDermott, John J.; et al. (European Union, 2000)
The extent and significance of trypanocidal drug resistance was investigated in priority areas of three East and Southern African Countries under a project. The project was built on the results of two previous projects. Existing methods currently available for the demonstration of drug-resistance, namely therapeutic tests in domestic livestock and rodents, and tests on trypanosome isolates in vitro, have particular drawbacks. In this project, these were supplemented with a novel approach, the use of ELISAs able to quantify the concentrations of trypanocidal drugs circulating in treated cattle.